Boney maroney - Morgan, Damian; Dale, Rae (Macmillan Education Australia South Yarra [Vic.], 1999)
Boney Maroney by Damian Morgan is a lighthearted and humorous novel that follows the adventures of a quirky protagonist named Maroney, who is known for his eccentric personality and unconventional lifestyle. The story explores Maroney's misadventures and his unique outlook on life, often leading to comical and unexpected situations. With witty dialogue and engaging characters, the novel touches on themes of individuality, friendship, and finding joy in the everyday oddities of life. Boney Maroney offers readers an entertaining and whimsical narrative filled with charm and laughter.